148k views
5 votes
Could someone please assist me​

Could someone please assist me​-example-1
User JKSH
by
5.2k points

1 Answer

4 votes

Answer:

See Below.

Explanation:

We are given that:


\displaystyle \cos(A - B) = \cos A\cos B + \sin A \sin B

Part 5.2.1

Note that:


\displaystyle \cos ( A + B) = \cos (A - (-B))

Then from the given identity:


\displaystyle \cos(A - (-B)) = \cos A \cos( -B) + \sin A \sin (-B)

Cosine is an even function and sine is an odd function. That is:


\displaystyle \cos(- \theta) = \cos \theta \text{ and } \sin (-\theta) = -\sin\theta

Hence:


\displaystyle \cos(A + B) = \cos A \cos B - \sin A \sin B

Part 5.2.2

We want to verify that:


\displaystyle \cos^2 (A - B) = 4\cos^2 B \sin^2 B

From the identity:


\displaystyle \cos (A - B) = \cos A \cos B + \sin A \sin B

Since A + B = 90°, A = 90° - B. Hence:


\displaystyle \cos (A - B) = \cos (90^\circ - B) \cos B + \sin (90^\circ - B) \sin B

Sine and cosine are co-functions. That is:


\displaystyle \sin \theta = \cos (90^\circ - \theta) \text{ and } \cos\theta = \sin(90^\circ - \theta)

Hence:


\displaystyle \cos (A - B) = \sin B\cos B + \sin B \cos B = 2\sin B \cos B

And by squaring both sides:


\displaystyle \cos ^2 (A - B) = 4\sin^2 B\cos^2 B

User Shanehoban
by
7.0k points